2022
DOI: 10.33884/basisupb.v9i1.5474
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay of Personality Factors and Language Learning Strategies in Developing Speaking Skill

Abstract: Speaking skill was one of essential parts in language learning and needed to be mastered by every student for a better foreign language communication. The aims of this research were (1) to find out the language learning strategies used by the students based on their personality factors (2) to observe the extent to which the personality factors and language learning strategies correlate with speaking skill, (3) to elaborate the interplay of personality factors and language learning strategies in developing stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Learning strategy is a method or approach used by teachers to organize students' materials, methods, media, equipment and time so that the learning process can run well, (Ragin et al, 20220;Santosa et al, 2020). In other side, it can be used as an equipment in language learning (Imansari et al, 2022). So it can be concluded that the teaching strategy is a method taken to achieve learning objectives.…”
Section: Learning Strategiesmentioning
confidence: 99%
“…Learning strategy is a method or approach used by teachers to organize students' materials, methods, media, equipment and time so that the learning process can run well, (Ragin et al, 20220;Santosa et al, 2020). In other side, it can be used as an equipment in language learning (Imansari et al, 2022). So it can be concluded that the teaching strategy is a method taken to achieve learning objectives.…”
Section: Learning Strategiesmentioning
confidence: 99%